Analisis Ketidaksempurnaan Bahasa dalam Fenomena Viral Bayi Monyet Punch: Kajian Pragmatik - Purba, Dela Pebina; Sihite, Yeni Fungky; Puspitarini, Herning; Siregar, Dwi Palentin; Nababan, Erika; Sigalingging, Febrina Dwiputri; Gaol, Rahel Naomi Lumban (Indo-MathEdu Intellectuals Journal, 2026)
The rise of social media has encouraged the use of language that is concise, informal and often grammatically incomplete, yet remains effective in conveying meaning. The viral phenomenon of the ‘Monkey Baby Punch’ serves as an interesting example of how linguistic imperfections are utilised in digital communication. This study aims to identify forms of linguistic imperfection in netizens’ comments and to analyse the pragmatic meanings contained within them. The study employs a descriptive qualitative approach. Data in the form of netizens’ comments were collected from various social media platforms using documentation techniques, then selected based on their relevance to the research focus. Data analysis was conducted through the stages of data reduction, classification of linguistic forms, and interpretation of meaning using George Yule’s theory of pragmatics and H. P. Grice’s concept of conversational implicatures. The results of the study indicate that linguistic imperfections manifest in the form of incomplete sentences, the use of informal language, and emotional expressions. Although structurally imperfect, the meaning remains comprehensible due to the shared context between the speaker and the reader. Furthermore, conversational implicatures were identified, demonstrated through the fulfilment or violation of the maxims of quantity, quality, relevance, and manner.